Karakteristik Bioplastik dari Pati Biji Durian dan Pati Singkong yang Menggunakan Bahan Pengisi MCC (Microcrystalline Cellulose) dari Kulit Kakao - Rozi Atifah Nur; Novizar Nazir; Gunarif Taib (Fakultas Pertanian, Universitas Warmadewa, 2020)
Starch-based bioplastics are safe for the environment. One source of starch that can be used is durian seed flour and cassava flour. Bioplastics made from starch have several disadvantages, so they need to be supported. One material that can be used for support is microcrystalline cellulose (MCC). This study aimed to determine the effect of mixing of durian seeds starch with cassava starch on the characteristic of bioplastic supported by MCC. This study used a Completely Randomize Design (CRD) with 5 treatments and 3 replications. Data were analyzed using analysis of variance (ANOVA) and continued with Duncan’s New Multiple Range Test (DNMRT) at 5% level. The treatment in this study was the mixing durian seeds starch with cassava starch (0%:100%, 20%:80%, 30%:70%, 40:60%, 50%:50%). The results showed that mixing durian seed starch with cassava starch significantly affected thickness and elongation. Based on the analysis of bioplastic characteristics, the best bioplastics were found in treatment E (addition of durian seed starch 50%: cassava starch 50%) with a thickness of 0.27 mm, tensile strength value of 7.17%, elongation of 0.13% and water absorption 91.46%.